Nutrition-related knowledge in a sample of Portuguese healthcare professionals - Sá, Carla (2020)
Food pattern can influence an individual's health status. One of the factors that influence diet behavior is nutrition-related knowledge. Although individuals benefit from dietary counseling, many healthcare professionals seldom have the knowhow to advise patients on nutrition-related features. The aim of this study was to evaluate nutrition-related knowledge in a sample of Portuguese Healthcare Professionals. METHODOLOGY: Distinct Healthcare Professionals (nurses; doctors; physiotherapists; [n= 38, 86.8% female, mean age: 40.1± 9.8 years]) from a Portuguese Local Health Unit, took part in this volunteered study. Nutritionrelated knowledge was assessed using the Portuguese reduced version of the Nutritional Knowledge Questionnaire. This version of the questionnaire consists of three sections (dietary recommendations [0-6 points]; sources of nutrients [0-34 points]; diet-disease relationship [0-16 points]), totaling a maximum score of 56 points. All participants gave their informed consent, and this work was approved by the ethics committee of the Local Health Unit. RESULTS: Our results indicate that 63.2% of Healthcare Professionals search for nutrition information less that once a month and 21% reported that took nutrition courses in addition to their basic training. Total score of the Portuguese reduced version of the Nutritional Knowledge Questionnaire was 30.8 ± 7.2 points. CONCLUSIONS: This sample of Portuguese Healthcare Professionals demonstrated reasonable nutrition-related knowledge. Interest in seeking information about nutrition was not evident and there was a low demand for the enhancement of nutrition-related knowledge. The integration of nutrition professionals in multidisciplinary teams could be a solution for the improvement of nutrition-related knowledge.